The drivers of intellectual capital in an agriculture, cattle and forest farmstead - Lopes, I. (Proceedings of the 6th European Conference on Intellectual Capital, 2014)
The pursuit of economic value, especially in the organizational context, has risen into a diversity of new concepts that reflect the genesis and importance that knowledge has been assumed in fields of companies’ strategies and performance. Intellectual capital has been emerged in the economic literature as knowledge capital which is embodied in knowledge-based organizations, driven them through multiple learning organizational processes. From a wholly accounting approach, it has been scanned and reported as intangible assets, source in itself of sometimes abnormal expected future returns. The identification of its multiple dimensions can be attained through two complementary orientations of thought: through a strategic approach, related to the creation and use of knowledge and its articulation with the dynamic value creation and, complimentarily, through the construction of new information systems and performance measures which are beyond the traditional financial approaches and measures. It is an approach that embodies the importance and the need to spread the unseen side of organizations. Its main aim is to translate and disseminate the companies’ real value, its own and invisible drivers, and identify the origin of their multiple inflows and returns. The company under analysis is the largest agriculture, cattle and forest farmstead in Portugal, covering several marshlands. The diversity of activities currently developed (Forest exploration; Hunting; Agriculture; Wines and olive oil production; and Tourism) requires an integrated research towards the construction and disclosure of its intellectual capital drivers. Through an experimental and interpretative case study approach, we seek for an integrated intellectual capital scorecard towards the organizational development and sustainability. In the first step of this research, it was possible to identify several sustainability drivers, namely forest management certification, commercial brands and awards, strategic alliances and networks, and biodiversity reputation.